A comparative study to assess the effect of intrathecal bupivacaine with morphine or butorphanol on post-operative pain relief following abdominal and vaginal hysterectomy (Health Renaissance, 2014)
Background: Post-operative pain management can be challenging. Objectives: To compare the efficiency of morphine with that of butorphanol in controlling the postoperative pain relief. Methods: This double-blind randomized clinical trial was performed on 75 consecutive patients. Intrathecal 3ml hyperbaric bupivacaine mixed with morphine (200 microgm-0.25ml); or mixed with butorphanol (200 microgm-0.25ml); or mixed with normal saline 0.25ml was administered to alternate groups (25 patients in each group), for postoperative pain relief after abdominal and vaginal hysterectomy. They were monitored for pain relief in the recovery and gynaecological ward for 24 hours. If the patient had any complications like nausea, vomiting, itching and urinary retention were recorded. Results: Time for two segment regression of sensory level in patients receiving intrathecal morphine (Group-M), was 114.0±12.2 min., intrathecal butorphanol (Group- B) was 96.0+24.4 min and normal saline (Group- N) was 104.4 ± 18.5min. Duration of pain relief after subarachonoid block In Group-M was 492.0 ± 153.2min, in Group- B 311.20 ±58.7min and in Group-N it was 299.4 ± 72.7min. Two patients (8%) in Group-M had nausea, vomiting and itching but none in other groups. Urinary retention occurred in 3 patients (12%), in Group- M, whereas the same was found in 2 patients (8%) and 1 patient (4%) of Group-B and N respectively. Conclusion: Intrathecal morphine provided prolonged and better analgesic effect after abdominal and vaginal hysterectomy than butorphanol, though there were some side effects like nausea, vomiting, itching and urinary retention which were graded by the patients as clinically not significant. DOI: http://dx.doi.org/10.3126/hren.v11i3.9640 Health Renaissance 2013;11(3):246-249